2019
DOI: 10.1038/s41418-019-0316-7
|View full text |Cite|
|
Sign up to set email alerts
|

Brf1 loss and not overexpression disrupts tissues homeostasis in the intestine, liver and pancreas

Abstract: RNA polymerase III (Pol-III) transcribes tRNAs and other small RNAs essential for protein synthesis and cell growth. Pol-III is deregulated during carcinogenesis; however, its role in vivo has not been studied. To address this issue, we manipulated levels of Brf1, a Pol-III transcription factor that is essential for recruitment of Pol-III holoenzyme at tRNA genes in vivo. Knockout of Brf1 led to embryonic lethality at blastocyst stage. In contrast, heterozygous Brf1 mice were viable, fertile and of a normal si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…An in vivo model with prostate epithelium-specific overexpression of BRF1 was generated by inter-crossing BRF1 mice [18] with the Pbsn (PB)-Cre4 strain [19] to generate PB-Cre4:BRF1 (herein referred to as BRF1 Tg ) mice (see Supplementary methods; Fig. 2a).…”
Section: Increased Brf1 Accelerates Prostate Tumourigenesis In Vivomentioning
confidence: 99%
“…An in vivo model with prostate epithelium-specific overexpression of BRF1 was generated by inter-crossing BRF1 mice [18] with the Pbsn (PB)-Cre4 strain [19] to generate PB-Cre4:BRF1 (herein referred to as BRF1 Tg ) mice (see Supplementary methods; Fig. 2a).…”
Section: Increased Brf1 Accelerates Prostate Tumourigenesis In Vivomentioning
confidence: 99%
“…Further, inactivation of the genes for the RPI factors Ubtf (ubtf) and Rrn3/TIF1A (rrn3) arrest mouse development during early cleavage stages (24,26). A similar argument could be made for inactivation of RPIII/PolIII transcription since loss of the Brf1 subunit of the TFIIIB complex also causes developmental arrest during early cleavage stages (49). We conclude that the maternal protein translation machinery is limiting in the cleavage embryo and must be replenished by zygotic expression to allow further development.…”
Section: Supporting Information Captions Supporting Resultsmentioning
confidence: 68%
“…Further analysis indicates that mutant MSK1 in either These studies demonstrate that MSK1 indeed mediates the activities of Brf1 and Pol III genes. Brf1 is a key factor which involves organ development [40]. Although our early studies have indicated that alcohol increases expression of Brf1 and Pol III genes of hepatocytes [7,33], it remains to be elucidated how alcohol affects Brf1 Oxidative Medicine and Cellular Longevity transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Brf1 is a key factor which involves organ development [ 40 ]. Although our early studies have indicated that alcohol increases expression of Brf1 and Pol III genes of hepatocytes [ 7 , 33 ], it remains to be elucidated how alcohol affects Brf1 transcription.…”
Section: Discussionmentioning
confidence: 99%